Studying the Effectiveness of Ribavirin® in the Experimental Form of Severe Acute Respiratory Syndrome - S. Ya. Loginova; V. N. Shchukina; S. V. Borisevich; R. A. Hamitov; V. A. Maksimov (Антибиотики и Химиотерапия)
The effectiveness of Ribavirin® was evaluated by the certainty of disease severity reduction and the coefficient of therapeutic action of drugs at the peak of the pathological process calculated by the following indicators: accumulation of the virus in the lungs, lung damage degree reduction, reduction observed in the severity of changes in the quantitative and qualitative characteristics of white blood, as well as the severity of changes in biochemical blood parameters. Ribavirin® is most effective when used according to the emergency prevention regimen at a dose of 20 mg/kg (therapeutic action coefficient — 70%); at a dose of 40 mg/kg according to the therapeutic and prophylactic regimen (therapeutic action coefficient — 60%). Increasing the dose of Ribavirin® did not contribute to the therapeutic effectiveness of the drug.